Boron-Containing Compounds as Antimicrobial Agents to Tackle Drug-Resistant Bacteria - Huang, Zongkai; Bai, Lang; Liu, Jie; Luo, Youfu (Pharmaceutical Fronts, 2024)
Bacterial infections, especially those caused by drug-resistant bacterial pathogens, are crucial diseases that damage human health. In recent decades, several important boron-containing drugs have been marketed as anticancer agents or anti-infective adjuvants. Among them, vaborbactam revitalizes the antibacterial effects of meropenem against bacteria by inhibiting β-lactamases, opening a new field for addressing bacterial resistance. In this article, the chemical features of boron atoms and the typical antibacterial agents and adjuvants of boron-containing compounds are reviewed. In this work, boron-containing agents are classified into four categories according to their action mechanisms: β-lactamase inhibitors, leucyl-tRNA synthetase inhibitors, LexA self-cleavage inhibitors, and NorA efflux pump inhibitors. This review provides actionable insights for addressing the increasingly severe drug-resistant infections of bacterial pathogens.
Keywords: boron-containing compounds; bacterial infections; drug-resistant; antibacterial agents; adjuvants